Academic Religious Studies and Anticolonial Protest: The Case of Ossetian Nativist Activism (Антропологический форум / Forum for Anthropology and Culture, 2021)
The article analyses the critique of the concept of ‘religion’ in two different intellectual projects. The first was undertaken by the social anthropologist Talal Asad, who constructed his examination of the conceptual apparatus of modern anthropology as a protest against the Eurocentrism of the contemporary social sciences and humanities. This critique made Asad a public intellectual, but not a social activist. The second case studied is the activity of Daurbek Makeev, and activist of the nativist religious movement in North Ossetia, who works on a revision of the dominant understanding of religion in Russian society. In the course of this work he treads a path from ethnic activist to public intellectual, with the prospect of occupying the social position of a regular academic student of religion. In conditions of an acute polemic with representatives of more powerful religious institutions, like some other activists of ethnic religions he seeks for new methods of legitimising his project in the eyes of society at large. These foundations are discovered in the existing academic practices of reviewing those academic positions which examine any religion from the perspective of its correspondence to a normatively understood Christianity. Reproducing to a large extent the arguments of the postcolonial critique of culture, Makeev seeks in the area of social sciences those theories of religion that could remove the opposition between the spheres of the religious and the secular, the individual and the social. He finds his theory in the approaches which discursively blur the boundary between academic practices and the techniques of spiritual searching and self-improvement, specifically in transpersonal psychology, which places scientist argumentation within the field of the spiritual searching of the New Age.